Swedish and Norwegian Police Interviewers' Goals, Tactics, and Emotions When Interviewing Suspects of Child Sexual Abuse - Magnusson, Mikaela (Front Psychol, 2021)
As the suspect interview is one of the key elements of a police investigation, it has received a great deal of merited attention from the scientific community. However, suspect interviews in child sexual abuse (CSA) investigations is an understudied research area. In the present mixed-methods study, we examine Swedish (n = 126) and Norwegian (n = 52) police interviewers' self-reported goals, tactics, and emotional experiences when conducting interviews with suspected CSA offenders. The quantitative analyses found associations between the interviewers' self-reported goals, tactics, and emotions during these types of suspect interviews. Interviewers who reported experiencing more negative emotions were more likely to employ confrontational tactics. Specifically, anger was positively associated with the goal of obtaining a confession and with aggressive tactics like raising one's voice and emphasizing the seriousness of the crime. Frustration and disgust displayed similar patterns. Somewhat contrasting these quantitative results, the thematic analysis identified a strong consensus that emotions should not and do not affect the police interviewers' work. Furthermore, the police interviewers described a range of strategies for managing emotions during the interview and for processing their emotional reactions afterwards. The present findings highlight the relevance of emotional processes in CSA suspect interviews and provide an initial exploration of the potentially complex relationship between the goals, tactics, and emotional experiences of police interviewers who question CSA suspects.